1985
DOI: 10.1111/j.1558-5646.1985.tb00420.x
|View full text |Cite
|
Sign up to set email alerts
|

Confidence Limits on Phylogenies: An Approach Using the Bootstrap

Abstract: The recently‐developed statistical method known as the “bootstrap” can be used to place confidence intervals on phylogenies. It involves resampling points from one's own data, with replacement, to create a series of bootstrap samples of the same size as the original data. Each of these is analyzed, and the variation among the resulting estimates taken to indicate the size of the error involved in making estimates from the original data. In the case of phylogenies, it is argued that the proper method of resampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
17,649
1
312

Year Published

1990
1990
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30,947 publications
(18,002 citation statements)
references
References 14 publications
40
17,649
1
312
Order By: Relevance
“…Since, we were assessing an intraspeciWc phylogeny, we adopted a model of evolution with as few assumptions as possible and selected Kimura-2-distance (Kimura, 1980). Topological conWdence was evaluated for both methods with 1000 bootstrap replicates (Felsenstein, 1985). Additionally, a network of haplotypes was constructed using the statistical parsimony method (Templeton et al, 1992) implemented in TCS (Version 1.21, Clement et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Since, we were assessing an intraspeciWc phylogeny, we adopted a model of evolution with as few assumptions as possible and selected Kimura-2-distance (Kimura, 1980). Topological conWdence was evaluated for both methods with 1000 bootstrap replicates (Felsenstein, 1985). Additionally, a network of haplotypes was constructed using the statistical parsimony method (Templeton et al, 1992) implemented in TCS (Version 1.21, Clement et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…A 10,000 permutations test against the null hypothesis indicated that phylogenetic signal did influence claw shape ( p  =   0.0034), so this relationship was investigated further. MorphoJ generated phylogenetically independent contrasts (PICs) as a way of measuring relative shape change decoupled from relatedness (Felsenstein, 1985; Klingenberg & Marugán‐Lobón, 2013). The output was in x‐y coordinates for each branching on the phylogeny.…”
Section: Methodsmentioning
confidence: 99%
“…Statistical supports for branches displayed by each of the two competing topologies were measured using 100 non-parametric bootstrap replicates (BP; (43)) and the approximate likelihood ratio test for branches (aLRT; (8)). BP and aLRT values (more precisely, pvalues obtained from SH tests) are reported on Fig.…”
Section: Assessing Statistical Support For Internal Edgesmentioning
confidence: 99%